(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
This study was conducted during the years (2016 and 2017) for the purpose of limiting the long-horned beetles Cerambycidae in the Green Mountain region, where five sites were selected in the region to collect some data on the species of this family using ground traps and other methods. The results obtained showed the presence of four subfamilies: Cerambycinae, Lepturinae, Lamiinae, Prioninae and nineteen genera belonging to this family, including: Phorcantha semipunctata, Stictoleptura cordigera, Hylotrupes bajulus, Rhesusser ricollis, Purpuricenus desfontiaine, Trichoferus fasciclata, Trichoferus griseus, Daramus mehennii, Icosium tomentosum, Macrotoma palmate, Penichroa fasciata, Cerambyx dux, Hesperophanes nassericus, Niphona pecticornis,. This study showed the periods of emergence of adult insects, which continued during the months of April, May, June, and August.